Strategi Peningkatan Inovasi Program Komunitas Literasi di Semarang (Studi di Bookclub Semarang) - Nurwidi Bagus Amiryunanto; Muhammad Rifqi Arviansyah (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
This study emphasizes how important literacy communities are to promoting a literacy culture in Kota Semarang, especially Bookclub Semarang. In light of Indonesia's inadequate national literacy performance, as evidenced by the 2022 PISA ratings, Bookclub Semarang has emerged as a novel platform for the community to improve literacy and knowledge. Interviews with members and management demonstrate that the programs provided by Bookclub Semarang efficiently meet the educational demands of the city's population. Regular efforts like Baca Buku Bareng (Reading Together) facilitate reading and book discussions while fostering good social relationships and a sense of belonging among participants. Innovative strategies are essential to maintain member involvement, organizational leadership, and community continuity. This study suggests program innovation strategies for community management and activities using SWOT analysis and innovation ambition matrix mapping. These tactics seek to enhance involvement among members and staff, guarantee the community's sustainability, and promote inclusion in nurturing reading interest throughout all demographics of Semarang's population. In the long run, these initiatives are anticipated to enhance the community's overall influence on literacy advancement.